The determinants of `domestic' original sin in emerging market economies - Arnaud Mehl; Julien Reynaud (European Central Bank (ECB), 2005)
This paper explains why domestic debt composition in emerging economies is risky. It carries out an analysis of the determinants of `domestic' original sin, which refers to the inability of emerging economies to borrow domestically in local currency, at long maturities and fixed interest rates. The latter is a measure of financial vulnerabilities arising from domestic debt composition, which encompasses maturity mismatches, rollover risk and interest payment contingency. The paper builds on a large dataset compiled by the authors from national sources. It finds that domestic original sin is severe when inflation is lofty, the debt service-to-GDP ratio high, the slope of the yield curve inverted and the investor base narrow. These results suggest that sound macroeconomic policies, attractive long-term yields and policies aimed at widening the investor base are instrumental to reduce domestic debt riskiness and tilt its composition towards safer, long-term, unindexed, local currency instruments.
Keywords: F34; F41; G15; 330; domestic debt; emerging economies; Original sin; Schulden; Öffentliche Schulden; Schwellenländer